PELATIHAN SIAP MENGHADAPI BENCANA DI SD MUHAMMADIYAH 1 DENPASAR BALI - Sri Muryaningsih; Agung Nugroho; Arifin Muslim (Yayasan Education and Social Center, 2023)
Disasters can be caused by natural events or man-made. Factors causing disasters include natural hazards and man-made hazards, which can be grouped into geological, hydrometeorological, biological, technological, and environmental quality degradation. The territory of Indonesia is located in a tropical climate region with two seasons, hot and rainy, which are characterized by extreme changes in weather, temperature, and wind direction. These climatic conditions, combined with diverse topography and soil types, result in fertile soil conditions. High population growth is not balanced with equitable and adequate economic, social and infrastructure policies and development, gaps in several aspects and sometimes social jealousy arises. This condition has the potential to cause conflicts in society that can develop into national disasters. Facing disasters requires the application of disaster preparedness education in schools with training. Disaster preparedness training is necessary for the school from the principal, teachers and students to understand how to evacuate themselves during a disaster so as to minimize casualties. The results of this community service activity are not in the form of objects but in the form of understanding and response to actions when facing disasters. Disasters cannot be predicted precisely because the nature of the occurrence of disasters is fast and there are slow disasters. There are also disasters that occur due to natural factors and occur due to human intervention